KEHIDUPAN WARIA DI KOTA DUMAI (Studi Kasus Waria Menghadapi Tekanan Sosial) - Nova Afrina; Ashaluddin Jalil (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Transvestites are men who prefer to play a role as women in their daily lives. Transvestites can be interpreted as analogous to the behavior of men who are graceful, soft and womanish .. The aim of this study was to identify and analyze the characteristics of transvestites, to know what are the social pressures experienced by transvestites and to know how or how transvestites face pressure social community. The theory used is the theory of aberration. Deviations are all actions that are not in accordance with the norms of social berlaku.Tekanan experienced by study subjects were from families and communities around such derision received by transvestites, the anger of families, punches and even evicted from the house by the family. Efforts made by the subject of research in facing social pressure is to run away from home to avoid ridicule from the local community and the anger and the blows that come from the family.Keywords: Sex, Deviant Behavior, effort and Pressure